West syndrome in patients with Kabuki syndrome (literature review and case report) - M. L. Zhitomirskaya; E. V. Snegova; G. V. Odintsova (Русский журнал детской неврологии)
Kabuki syndrome (KS) is a rare genetic disorder that has facial phenotypic descriptors, retarded growth, various malformations and different degrees of intellectual disability.Objective: to study the characteristic features of KS comorbid with West syndrome according to literature review and data collection together with KS described clinically, and treatment success rates by the clinical case study research.There was conducting literature review on the topic in the databases OMIM, PubMed, Scopus, and e-library. The articles describing cases of epilepsy in patients with KS were analyzed. We conducted our own observation of KS in the male patient with epilepsy and West syndrome in a patient with KS was analyzed by the clinical case study research.Kabuki syndrome comorbid with West syndrome increases neurological deficits and leads to the formation of a marked delay in mental and speech development and psychomotor development retardation. Peculiarities of the treatment of KS comorbid with West syndrome are the lack of efficacy of antiepileptic drugs, and the very visible effectiveness of the ketogenic diet, together with an atypical response to hormone replacement therapy in the form of distinct positive dynamics – a clinically meaningful reduction in seizure frequency along with elevated liver enzymes.